A Complex Cardiac Mass Originating from Interatrial Septum in a Patient with History of Kidney Cancer: A Case Report and Literature Review - Negar Faramarzi; Sumit Sohal; Roshanak Habibi; Muhammad Sikander Akbar (Case Reports in Cardiology)
Cardiac tumors are a rare phenomenon, and most cases are secondary to metastatic cancers rather than primary tumors. Renal cell carcinoma (RCC) is notorious for metastasis to cardiac tissue. Tumor thrombus migration to the renal vein and inferior vena cava happens in up to 10% of patients with RCC. Transitional cell carcinomas are another form of renal cancer, which may metastasize to the heart and are associated with widespread metastasis. Here, we report a patient with a past medical history of metastatic transitional cell cancer of renal pelvis under treatment with checkpoint inhibitor therapy presenting with shortness of breath. He had disseminated metastasis to bones, pleural space, lungs, and muscles. A large mass was found in the interatrial septum with invasion to the right and left atrium. The mass had a cystic component protruding into the left atrium. He passed away a few days after presentation.